Instalação-jardim na escola pública: uma experimentação em artes visuais usando materiais alternativos, sustentáveis e de baixo custo - Costa, Emanuel Guedes Soares da (2022)
The research sought to investigate possibilities of artistic experimentation based on alternative supports, materials or inputs, for experimentation in Visual Arts, through sustainable practices, reuse, recycling, or lower cost, taking into account the context and supply of materials in the locality of application of the study that culminated in the creation of a garden-installation. For each point to be discussed, we used specific theoretical references: the use of the triangular approach in artistic practice and experimentation, obstacles to artistic practice in the school context, sustainability and added values, materials and modalities, construction and understanding of installation-garden concept. Seven 8th grade students participated in the research, from the Municipal School of Early Childhood Education and Elementary Education Professora Maria Tereza da Conceição, located in the district of Curimataú, municipality of Pilar, state of Paraíba - PB. The research aimed to identify materials and supports observing applicability both in traditional or contemporary two-dimensional and three-dimensional modalities based on what the context of the community guiding us by concepts of sustainability and added values or low cost as an alternative way to the problem of lack or scarcity of materials. We raised the following hypotheses: the possibility of alternative development of materials aimed at artistic making in Visual Arts, these can contemplate all or in parts the sustainability, low cost, recycling or reuse characteristics; practices only allow two-dimensional and traditional experiments in schools, such as painting and drawing; the options explored only foment compositions with a contemporary approach such as installations, objects or performances; the availability of materials found in the community allows for both traditional and contemporary applications. The choice of institution and location was due to the difficulty of access or lack of materials and supports for artistic experimentation given the logistical or financial precariousness. To this end, the application methodology made use of research instruments (questionnaires, lists and experiments) supported by the vertices of the Triangular Approach, both in the analysis of artistic works and in the observation of the context and the data collected. Also, workshops on material handling and production of alternatives were developed, combined with moments of contextualization and appreciation of artistic works and traditional and contemporary techniques. The analysis and discussion of the experiments obtained culminated in the final product (garden-installation) based on the elements collected by the student-participants and permeated by concepts of environmental awareness through sustainable thinking and actions, recycling, reuse or low cost. As well as the classification of the term garden-installation, since it would facilitate the understanding and intervention possibilities of the users before the proposal.